Literacy Understanding of Sharia Capital Markets among High School Students and Teachers: An Empirical Model of Determinant Factors - Sholihin, Muhammad; Ilhamiwati, Mega; Andriko, Andriko; Sulastri, Eva; Ferdinand, Rio (Indonesian Center for Religion and Society Studies (InTReSt), 2024)
This study aims to identify the factors that affect sharia capital market literacy among high school students and teachers. Using a quantitative approach, as many as 38 teachers and students in Curup City, were surveyed to analyze the influence of variables such as education level, investment experience, information sources, financial knowledge, family support, investment motivation, and religious understanding on sharia capital market literacy. The results of the study show that family support, ease of access to information, and religious understanding have a significant influence on sharia capital market literacy. The factors of education and investment experience did not show significant influence, suggesting that practical experience and knowledge were more important than formal theory. The implications of Islamic financial education policies and recommendations to improve financial literacy among students and teachers are discussed further.